2002
DOI: 10.1038/sj.onc.1205072
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase as a therapeutic target for malignant gliomas

Abstract: Telomerase, a ribonucleoprotein enzyme, is considered as a potential target of cancer therapy because of its preferential expression in tumors. In particular, malignant gliomas are one of the best candidates for telomerasetargeted therapy. It is because malignant gliomas are predominantly telomerase-positive, while normal brain tissues do not express telomerase. In theory, there are two telomerase-associated therapeutic approaches for telomerase-positive tumors. One approach is the antitelomerase cancer therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 74 publications
0
45
0
1
Order By: Relevance
“…In addition, the level of hTERT transcripts appears to predict in GBMs decreased or increased survival. In the development and future application of anti-telomerase treatments of malignant gliomas (Komata et al, 2002), hTERT analysis of any given tumour will be essential.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the level of hTERT transcripts appears to predict in GBMs decreased or increased survival. In the development and future application of anti-telomerase treatments of malignant gliomas (Komata et al, 2002), hTERT analysis of any given tumour will be essential.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, telomerase has been recognized as a new wide-range tumor marker (Blackburn, 1991;Komata et al, 2002). It has been reported that telomerase activity is significantly higher in about 90% of cancers and correlates well with the degree of malignancy (Kim et al, 1994;Shay, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas normal somatic cells have diminished telomerase activity, Ͼ90% of human cancers overexpress telomerase (5,6). The well established roles for telomerase in tumor initiation and cellular immortalization (7,8) have led to the identification of telomerase as a potentially important molecular target in cancer therapeutics (9)(10)(11). To date, multiple studies have examined the utility of targeting telomerase to inhibit tumor cell proliferation (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%